Evaluation of the Nutritional, Minerals, and Antioxidant Potential of Roselle (Hibiscus sabdariffa Linn.) Seeds from Roi Et Province in the Northeastern Region of Thailand - Phewphong, Sunti; Roschat, Wuttichai; Namwongsa, Krittiyanee; Wonam, Aonuma; Kaisri, Thapanapong; Duangpakdee, Patsorn; Leelatam, Tappagorn; Moonsin, Preecha; Promarak, Vinich (Trends in Sciences, 2023)
In Thailand, the roselle seeds have a few utilizations other than seeds for planting propagation. Consequently, this study aimed to evaluate the nutritional and mineral profile of roselle seeds in the Northeast region of Thailand. The obtained results proved that roselle seeds were found to be a good source of carbohydrates (41.48 ± 0.31 %), protein (30.40 ± 0.09 %), and fat (19.70 ± 0.04 %). Additionally, the results indicated that roselle seeds were a rich source of fiber (40.61 ± 0.26 %) and had a high energy content (1945.03 ± 12.31 KJ/100 g of sample). The macronutrients and micronutrients of the roselle seeds, such as K, P, Mg, Zn, Fe, Mn, and Cu, were found to be 2092.50 ± 1.89, 891.22 ± 3.71, 366.00 ± 1.34, 7.17 ± 0.13, 6.81 ± 0.20, 5.88 ± 0.14 and 4.22 ± 0.11 mg/g of sample, respectively. Furthermore, the total phenolic compounds as bioactive components and DPPH radical scavenging capacity were equal to 21.22 ± 0.24 mg GAE/100 g of sample and 46.28 ± 1.35 %, respectively. Thus, the roselle seeds were considered a cheap nutrient source and could be a good source of potential food ingredients. HIGHLIGHTS The roselle (Hibiscus sabdariffa) seeds derived from Roi Et Province in the Northeast region of Thailand have a highly rich source of nutrients, bioactive compounds, and minerals The roselle seeds were considered a cheap nutrient source and could be a good source of potential food ingredients GRAPHICAL ABSTRACT